Incidence of injuries in young soccer players: epidemiological study in an Italian elite club - Thiébat, G.; Spreafico, A.; Mazzoni, S.; Ravasio, G.; de Girolamo, L.; Schoenhuber, H. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Football is the most popular sport in the world, increasingly played by the youngsters. However, little epidemiological data exists regarding injuries in young players. The aim of this study was to describe the most common types and sites of injury among the different classes of a single professional football club. METHODS: The present perspective study covered a three-season period, including 679 children divided in 9 age classes. All the athletes were managed by the same staff and for each injury, onset date, date of return to training, anatomic site and type of injury were recorded. RESULTS: The mean age of the population was 12.7 years old (Range 7.4-16.9). A total 975 injuries were recorded without significant differences among seasons (P=0.682). The most affected classes were U17 and U16, while the lowest rate of injury was in U11. The most common injury in U9 and U10 affected foot and ankle, while in all the other classes thigh was the most frequently site involved. Focusing on the type of injury, the most common cause was traumatic (40.9%), followed by muscular diseases. The mean value of absence from soccer was 19.7 days (±1.2). The highest rate of injuries occurred in September and August. In January and February, injuries were more frequent during competitions, whereas in the other months the rate was inverted. CONCLUSIONS: This study highlights that preseason and the final phase of the season are more at risk of injury and the type of injury differs between classes.